AN EXTRINSIC DISPOSITIONAL ACCOUNT OF VULNERABILITY - ARMSTRONG, FRÉDÉRICK (Les ateliers de l'éthique / The Ethics Forum, 2017)
It is common to see vulnerability as either “ontological” or broadly “circumstantial.” Both views capture something morally important about vulnerability. However, there is a puzzle: how can the same concept refer to a necessary ontological fact and to a contingent circumstance? I address two solutions to this puzzle. First, I argue that Mackenzie et al.’s taxonomy of vulnerability is not a real solution (2013). Second, I address Martin et al.’s dispositional account of vulnerability (2014). For them, vulnerability is both an intrinsic property and a disposition. This supposedly solves the puzzle: vulnerability can be intrinsic and yet be manifest in only some circumstances—such is the nature of dispositions. However, I argue that if vulnerability is indeed a disposition, it is better conceived as an extrinsic disposition (McKitrick 2003). Thus, vulnerability cannot be both intrinsic and dispositional; Martin et al. fail to resolve the puzzle. This, however, is no reason to fret. Indeed, an amended dispositional account of vulnerability, in which it is conceived as an extrinsic disposition, is metaphysically consistent and it satisfies our moral intuitions about human vulnerability, and more. Given these advantages, I argue the solution to this dilemma is to abandon the ontological conception of vulnerability.